PERAN GURU PENDIDIKAN PANCASILA DAN KEWARGANEGARAAN DALAM MEMBINA KEDISIPLINAN PESERTA DIDIK DI SEKOLAH MELALUI PENDEKATAN KETAULADAN GURU PADA KELAS X.IPA DI SMA NEGERI 1 PADANG BOLAK JULU TAHUN AJARAN 2023-2024 - Husein Nst, Ahmad; Mayasari, Enni (Universitas Muhammadiyah Tapanuli Selatan, 2025)
Based on theresults of data collection activities, data processing, and analysis of learning result test data, the role of Pancasila and Citizenship education teachers in fostering discipline obtainedan average score of 42.240 and a standard deviation of 0.522, while in fostering student discipline in schools through a teacher example approach, theaverage score wasobtained. mean 27,400 with a standard deviation of 1,154. Based on thefirstcycle of classaction in learning management, itwas 77.5% and in the second cycle therewasan increase to 97.5%, theresults of data acquisition show edthat therewas a difference. From theresults of activities in fostering student discipline in school sthrough the teacher exampl eapproach, 82% wasobtained and in the second action carriedout, 95.10% was obtained. Mean while, thet table value distribution table isbased on SPSS with the number of samples or df-(n-2) meaning (N) 25 -2 = 23 with r 0.05 of 0.3365 so that the significant valueisr count (0.001086) > rtable (0.3365) meaningit has aneffecton variable Y. So based on theresults of studenttests and hypothesis testingit can be concluded thatthe role of theteacher Pancasila and Citizenship education in fostering student discipline at school through a teacher example approach in class X.IPA at SMA Negeri 1 Padang BolakJuluforthe 2023-2024 academic year. So withthe role of Pancasila and Citizenship Education teachers, they can Foster students to increase their discipline with theleadership of Pancasila and Citizenship Education teachers